De lijst van Dubuffet meesterwerken uit de Prinzhorn Collectie = Dubuffet's list : masterpieces from the Prinzhorn Collection - Beyme, Ingrid von 1962-; Röske, Thomas 1962-; Brun, Baptiste ca. 20. Jh; Looijen, Hans (Museum Het Dolhuys, 2017)
Dubuffet's List: Masterpieces from the Prinzhorn Collection" at Amsterdam's Outsider Art Museum offers the unique opportunity to view the earliest collection of Outsider Art in Europe and also offers fresh insights into the encounter between the ideas of psychiatrist Hans Prinzhorn and those of the founder of art brut, Jean Dubuffet. Dubuffet viewed the impressive Prinzhorn Collection as a forerunner of his own Collection de l'Art Brut, so his visit to Prinzhorn's collection was a long-cherished dream. Prinzhorn considered the works from an academic standpoint, while Dubuffet viewed the collection from the viewpoint of an artist and collector. Exhibition: Outsider Art Museum, Amsterdam, The Netherlands (22.06.-24.09.2017)
Catalog of an exhibition held at the Outsider Art Museum, Amsterdam, June 22 - September 24, 2017 [Ausstellungsdaten ermittelt]
Keywords: Klinik für Allgemeine Psychiatrie -- Sammlung Prinzhorn; Prinzhorn, Hans / 1886-1933 / Art collections / Exhibitions; Dubuffet, Jean / 1901-1985 / Exhibitions; Dubuffet, Jean / 1901-1985; Prinzhorn, Hans / 1886-1933; Outsider art / Europe / Exhibitions; Art brut / Europe / Exhibitions; Art, European / 20th century / Exhibitions; Art brut; Art, European; Art / Private collections; Outsider art; Europe; 1900-1999; Exhibition catalogs; Ausstellungskatalog -- Outsider Art Museum -- 22.06.2017-24.09.2017 -- Amsterdam; Bildband; Katalog